Utility of 'back‐up' arterio‐venous fistulae in patients on peritoneal dialysis and use of haemodialysis catheters. Issue 7 (18th July 2021) - Rao, Nitesh N.; Borlace, Monique; Taylor, Rebecca; Matthew, Yvonne; Johnson, David W.; Jaffrey, Lauren; Mudge, David W.; Bannister, Kym
Abstract: Background: Patients undergoing peritoneal dialysis may require unanticipated transfer to haemodialysis. Back up fistula are often created in selected patients. These may help reduce the infective burden of haemodialysis (HD) catheter. Aim: To study the utility of back‐up arterio‐venous fistulae (AVF) in patients initiated on peritoneal dialysis (PD) and to determine the rates of HD catheter use in patients requiring conversion to HD. Methods: Data on HD transfer and HD catheter usage were retrospectively analysed in all patients initiating PD between January 2010 and December 2014 at Royal Adelaide Hospital (RAH; universal back‐up AVF creation at PD commencement) and Princess Alexandra Hospital (PAH; selective back‐up AVF creation in 'high risk' patients). Results: A total of 374 patients initiated PD during the study period: 142 in RAH group and 232 in PAH group. The groups were reasonably comparable, except that RAH patients were more likely to be older, Caucasian and diabetic. Transfer to HD occurred in 33 (23%) patients in RAH group and 99 (43%) in the PAH group with respective median times to HD transfer of 289 and 295 days. HD catheter usage was required at the time of HD transfer in 11 (33%) patients at RAH and 64 (65%) in patients at PAH ( P < 0.001). AVF complications occurred in 13 (9%) patients in RAH group (fistuloplasty n = 8, transposition n = 2, ligation due to ischaemia n = 2 and construction of new AVF n = 1). Conclusion: Patients undergoing PD frequently require urgent unanticipated transfer to HD and back‐up AVF can be successfully utilised in this setting in the majority of cases, which in turn can reduce the infective burden of HD catheter exposure.